Effect of Residual Cake Steryl Glucoside Co-Firing Ratio on Boiler Combustion, Efficiency and Fuel Cost - Valentino, Andreas Alvaro; Hadiyanto, Hadiyanto; Suedy, Sri Widodo Agung (Universitas Ibn Khaldun Bogor, 2026)
Steryl Glucosides (SG) are compounds produced from the processing of Fatty Acid Methyl Ester (FAME). SG compounds are obtained from the FAME filtration process using filter aid media. The filtering process produces residue in solids mixed with SG compounds (residual cake SG). Previous studies have shown that SG has a high calorific value and good combustion characteristics. However, the research is still on a laboratory scale. Another study states SG has a high energy density due to its characteristics, which include a long hydrocarbon chain. These make SG very potential to be utilized as a secondary co-firing fuel in boilers. Implementing co-firing could minimize coal consumption and lead to a reduction of carbon emissions. Furthermore, several studies found that co-firing could increase the boiler efficiency and reduce the fuel cost. This study aims to determine the effect of the residual cake co-firing ratio on the combustion, efficiency, and fuel cost of the stoker boiler. The research was conducted directly on the stoker boiler with a ratio of residual cake SG 5 wt%, 10 wt%, and 15 wt%. Based on the trial, increasing the residual cake SG ratio will improve the boiler combustion, increase efficiency up to 8%, and reduce the fuel cost.